KOHESI DAN KOHERENSI PADA KARANGAN DESKRIPSI SISWA KELAS VII SMP N 15 YOGYAKARTA - Putri Purbowati; Risa Puspitarini; Anang Dwi Cahyono; Hardiyanti Kusrini (PIKTORIAL : Journal of Humanities, 2019)
Cohesion is a semantic concept that displays the relationship of meaning between text elements. The relationship occurs because the meaning of one element of the text depends on other elements. Without the cohesion of the discourse, the text is not considered communicative and every element in it is interconnected. Coherence in sentences or paragraphs is the relationship between elements contained in a text. This research is descriptive qualitative research. This study uses a description of eighth-grade students of SMP N 15 Yogyakarta. The subjects of this study are the sentences in the writing of students' essays description. The object of this study is a marker of cohesion and coherence relationships used by students, including types, and how variations in their use. The design of this research is descriptive qualitative. Data collection techniques are done by reading and note-taking techniques. The method of analysis uses descriptive qualitative analysis methods. The instrument used in this study was a human instrument. The results of this study indicate that the total number of errors found was 10 errors consisting of six cohesion errors and four coherence errors. Keywords: cohesion, coherence, description essays